Pengaruh Penggunaan Media Manipulatif terhadap Kemampuan Berhitung Permulaan Siswa Kelas 2 Sekolah Dasar - Mukti, Rayi Arista; Fithri, Wardatul; Tambunan, Apriyani Br; Situmorang, Mulyani Br; Irfan, Irfan (MASALIQ, 2023)
Counting is often considered a difficult and unpleasant subject, it is necessary to use manipulative media in order to make learning to count more interactive, interesting and easily understood by students. This study aims to analyze the effect of the use of manipulative media on the numeracy skills of grade 2 students at SD Negeri 54/I Bajubang. This study uses a qualitative method with a type of phenomenological research. The research was conducted from March to April 2023. The subjects in this study totaled 21 students, all students were grade 2 students at SD Negeri 54/I Bajubang. The research data is in the form of descriptions, the data collection instruments used are observation sheets, oral tests and documentation. The data analysis technique used in this study is a comparison technique. Prior to the use of manipulative media in learning, each student only mastered a few indicators of initial numeracy skills. After using manipulative media in learning, each student is able to master all indicators of initial numeracy skills. This shows that manipulative media can improve students' ability to understand learning to count. Manipulative media in learning fosters students' motivation and interest in learning.